2007
DOI: 10.1016/j.gene.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and initial characterization of African green monkey (Cercopithecus aethiops) corticotropin releasing factor receptor type 1 (CRF1) from COS-7 cells

Abstract: We report the expression of endogenous CRF1 in COS-7 cells (African green monkey origin). Cloning of the coding region of CRF1 gene identified three alternatively spliced isoforms with nucleotide and predicted amino acid sequences corresponding to the membrane bound α and c and soluble e isoforms. DNA sequencing of the main isoform CRF1α showed homologies of 99%, 97% and 91% with the rhesus monkey, human and rodent genes, respectively; the deduced protein sequence differed in only one amino acid with Rhesus mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…Recent studies revealed that the expression of the elements of the HPA-axis is not limited to the neuroendocrine system, but its elements are also found in immune cells (Slominski, 2006; Slominski et al ., 2000b), the digestive system (Tache & Bonaz, 2007), the skin and its appendages (Slominski & Mihm, 1996; Slominski et al ., 1996b; 2007a), the reproductive system (Hillhouse & Grammatopoulos, 2006) and many other tissues (Slominski et al ., 2000b; 2007b; Hillhouse & Grammatopoulos, 2006; Zmijewski et al ., 2007). …”
Section: Hpa Axismentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies revealed that the expression of the elements of the HPA-axis is not limited to the neuroendocrine system, but its elements are also found in immune cells (Slominski, 2006; Slominski et al ., 2000b), the digestive system (Tache & Bonaz, 2007), the skin and its appendages (Slominski & Mihm, 1996; Slominski et al ., 1996b; 2007a), the reproductive system (Hillhouse & Grammatopoulos, 2006) and many other tissues (Slominski et al ., 2000b; 2007b; Hillhouse & Grammatopoulos, 2006; Zmijewski et al ., 2007). …”
Section: Hpa Axismentioning
confidence: 99%
“…CRF is synthesized predominantly in the paraventricular nucleus of the hypothalamus, but it was also found in the peripheral tissues, including: reproductive organs (Asakura et al ., 1997; Clifton et al ., 1998), liver, stomach, spleen, adrenal and thyroid glands, bowel (Slominski et al ., 2000b; Charmandari et al ., 2005; Hillhouse & Grammatopoulos, 2006), retinal pigment epithelium (Zmijewski & Slominski, 2009a), kidneys (Slominski et al ., 2007b) and skin (Slominski et al ., 2001; 2006b). Its expression is stimulated by several neurotransmitters (serotonin, acetylcholine) (Ohmori et al ., 1995; Laflamme et al ., 1999), neuropeptides (arginine vasopressin, neuropeptide Y, enkephalin) (Itoi et al ., 1999) and cytokines (tumor necrosis factor (TNF), interleukins 1 and 6) (Turnbull & Rivier, 1999; Slominski, 2006).…”
Section: Crf Receptors and Their Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we postulated that such a variety of phenotypic effects of CRF may be explained by cell type dependent expression of multiple isoforms of the CRF receptors type 1 and 2. 32,36,[75][76][77][78][79][80][81] At least…”
mentioning
confidence: 99%